(untitled) (Research, Society and Development, 2021)
The family context significantly influences the child development process. The way in which families experience the evolutionary stages of life, influence the way of coping with the diversity that intervenes in parental relationships. Thus, studies focused on parenting practices and the means of learning to better understand relationships, have considerable social relevance. This article aimed to find evidence of validity of interventions in groups aimed at parental guidance of parents and / or caregivers of children. An integrative review comprising 17 articles from the VHL, LILACS and SciELO databases was carried out. The results showed that the parental guidance carried out in groups of parents generated brought benefits to the families, considering that this practice favors learning opportunities, emotional support to its members, reframing the forms of communication used in the interactions between parents and children, and a better knowledge on the part parents about the means used by them to prevent and cope with dysfunctional behaviors and how it interferes with the children’s well-being. However, despite the diverse benefits of parental guidance groups, the articles feature bring great methodological differences. Thus, it is concluded that more interventional studies on parental groups and the training techniques of parents in the age group proposed in the family, school and other contexts in that the family is inserted are still necessary.